Impacts of psychological stress on high dose-rate radiation acute effects in a mouse experimental model. (20th June 2022) - Nakajima, Tetsuo; Ninomiya, Yasuharu; Unno, Keiko; Morioka, Takamitsu; Nishimura, Mayumi; Kakinuma, Shizuko
Abstract: Psychological stress affects health. Radiation workers in the medical field or astronauts living in space have possible risks of exposure to radiation, and psychological stress is considered to be easily induced in them due to activities performed in small areas or stress conditions. The impact of psychological stress on the effects of radiation was evaluated in senescence-accelerated mouse prone 10 (SAMP10) mice and ddY mice using a confrontational housing model, which makes dominant and subordinate mice in a cage live together without severe quarrel. Mice of ddY and SAMP10 have been previously demonstrated to be influenced in terms of acute and late effects, respectively, under psychological stress by this model. In SAMP10 mice, irradiation with 4 Gy induced the death of irradiated mice under psychological stress. In ddY mice, irradiation with 5 Gy X-rays alone had almost no effect on the mouse survival, but irradiation in conditions of psychological stress promoted acute death of irradiated mice. In addition, hypocellular bone marrow was also observed histopathologically in irradiated ddY mice under stress. Psychological stress may promote damage caused by radiation through modulation of radio-sensitivity in bone marrow in mice. This model would be useful for evaluation of modulation of radiation-induced various effects by psychological stress.